Психолого-педагогические условия обеспечения качественного образования детей с ограниченными возможностями здоровья в образовательных организациях новосибирской области - Дробышева Е. С.
In the article analyzing the quest ions connected with psychological and pedagogical conditions which have to be created in the educational organization for training persons with limited opportunities of health. Creation of psychological and pedagogical conditions for education of children with limited health opportunities decides by the exist ing legislative and other regulations in education of the Russian Federation.
Keywords: Дети с ограниченными возможностями здоровья